If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -4 = 8x + 3 Reorder the terms: -4 + x = 8x + 3 Reorder the terms: -4 + x = 3 + 8x Solving -4 + x = 3 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -4 + x + -8x = 3 + 8x + -8x Combine like terms: x + -8x = -7x -4 + -7x = 3 + 8x + -8x Combine like terms: 8x + -8x = 0 -4 + -7x = 3 + 0 -4 + -7x = 3 Add '4' to each side of the equation. -4 + 4 + -7x = 3 + 4 Combine like terms: -4 + 4 = 0 0 + -7x = 3 + 4 -7x = 3 + 4 Combine like terms: 3 + 4 = 7 -7x = 7 Divide each side by '-7'. x = -1 Simplifying x = -1
| 4x+9y = 4y+17 | | 0=2x^2+2 | | 4a+11/3=16a | | -3x-1=5-2x | | (5n+2)(2n-3)= | | 16x^4+6x^2= | | (3x-4)(x-2x^2-6)= | | (3-2y)(8-y)= | | (y-9)(y+9)= | | (m+1)(m+1)= | | (a-5)(a+3)= | | 3r(r-5)-2r(3r-1)= | | -2a(3a^2-4a-1)= | | 5(2x-11)+17=52 | | 5x(4x-3)= | | 9x-10y=-7 | | 10(x-1)/2x+10x=5 | | (3p^2-q^2)-(4p^2-7q^2)= | | 8(x+3)+7=71 | | (4x^2+5x+1)-(3x^2-7x+4)= | | 29.25/0.36 | | (-3m^2+8n^2-6n)-[(8m^2-6m+2n)+(-8m^2)+4n^2]= | | 144+81= | | 5xn=4.5 | | 10(x-1)/2x+10 | | x=12+9 | | 45/18=9/x | | -4/5*(4*-34/4-1) | | (2)/(2x-5)=-2 | | -1/4x^2-x-8=0 | | -34/4 | | 2x+5x=-15x-6x |